Perinatal results of restricted intrauterine growth. Cienfuegos, 2022 - Cristóbal Jorge Torres González; Vivian Rosa Vázquez Martínez; Ana Beatriz Abreus Castro; Yaneris Vega Romero; Greter Torres Vázquez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Foundation: restricted intrauterine growth requires intensive prenatal management to determine fetal status and delivery time. Objective: To describe the perinatal outcomes of restricted intrauterine growth. Methods: case series study developed at the Cienfuegos Hospital in 2022. The studied variables were: type of delayed intrauterine growth, results of Doppler ultrasound in maternal and fetal vessels, diseases that complicated the pregnancy, type of delivery, weight and gestational time to delivery, adverse perinatal outcomes. The distribution of clinically important variables was compared with adverse perinatal outcomes. Results: delayed growth affected 4.7% of births, 25% had early onset; 17.3% had preeclampsia, 41.3% had MPI ArUt >95 p. 14.4% of fetuses presented alterations in Doppler flows (ICP<5 p with 42%); 98% had restricted growth grade I. 19% of pregnant women needed termination of pregnancy at week 34 or before. A cesarean section was performed in 44.6% and 18.7% of live newborns required admission to the NICU; there were three neonatal deaths and two late fetal deaths. Adverse perinatal outcomes were more frequent in fetuses with ICP<5 p, delivery before 34 weeks and birth weight less than 1500 g (p<0.05). Conclusions: the alteration of the cerebroplacental index in the fetus, birth before 34 weeks and weight less than 1500 g at birth, increases the adverse perinatal risk in fetuses/neonates with restricted intrauterine growth.